2013
DOI: 10.1038/sc.2012.171
|View full text |Cite
|
Sign up to set email alerts
|

Application of transanal irrigation for patients with spinal cord injury in South Korea: a 6-month follow-up study

Abstract: Study design: A 6-month follow-up study. Objectives: To investigate the outcome of transanal irrigation (TAI) in patients with spinal cord injury (SCI) and to identify factors significantly related to clinical success. Setting: Survey for community-dwelling patients with SCI in South Korea. Methods: Between December 2010 and March 2012, TAI was initiated with 52 patients (41 men; age: 44.5 ± 11.0 years) with neurogenic bowel dysfunction (NBD). At 1, 3 and 6 months after initiation, a telephone interview was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…Most experienced practical problems such as burster/expulsion of the rectal catheter and financial problems. These results were similar to those of Kim's study 26 that indicated practical problems with TAI in 63.5% of patients; in 48.1%, the problem was expulsion of the rectal catheter. Balloon burst and expulsion have already been reported previously in the literature (33-77%).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Most experienced practical problems such as burster/expulsion of the rectal catheter and financial problems. These results were similar to those of Kim's study 26 that indicated practical problems with TAI in 63.5% of patients; in 48.1%, the problem was expulsion of the rectal catheter. Balloon burst and expulsion have already been reported previously in the literature (33-77%).…”
Section: Resultssupporting
confidence: 81%
“…6,10,11,15,26 However, anorectal pain, nausea, headache and other symptoms were not reported in any case in this study. There are documented risks associated with TAI, which include systemic reactions to irrigation solutions and rectal perforation, 9 but these adverse effects were not noted in our study.…”
Section: Resultsmentioning
confidence: 48%
See 2 more Smart Citations
“…Unfortunately, other authors have shown that patient compliance with this method can decrease over time. 15 Digital rectal stimulation, another bowel management technique, involves the use of a gloved finger inserted into the anorectal canal. This has been shown to enhance contractions of the descending colon and rectum, contributing to bowel evacuation.…”
mentioning
confidence: 99%